Risk Factor Assessment of Software Usability Using Fuzzy-Analytic Hierarchy Process Method - Afriyanti Dwi Kartika; Sofia Umaroh (JURNAL INFOTEL, 2018)
Software adds significant value to a wide range of products and services. Thus, in the process of software development, maintaining the quality of the software is an important aspect that the developer must do. In several software quality models, usability is stated as one of significant factor that gives impact to software performance. The existence of problems in usability will lead to less useful of the software. This research was conducted to assess software usability risk factors which derived from the attributes and sub-attributes of usability, that affecting the quality of the software negatively. The importance of risk factors assessed by using fuzzy-AHP that was used to identify the dominant factor that become the source of risk. The risk assessment on software usability with fuzzy methodology made it possible to process the evaluation of the respondents defined by linguistic format, in which information can be processed from the data were insufficient. This fuzzy methodology allowed to process the data that were subjective, inaccurate or vague.